2010
DOI: 10.1021/nl1003587
|View full text |Cite
|
Sign up to set email alerts
|

Single-Order, Subwavelength Resonant Nanograting as a Uniformly Hot Substrate for Surface-Enhanced Raman Spectroscopy

Abstract: The surface-enhanced Raman spectroscopy (SERS) activity and the optical reflectance of a subwavelength gold nanograting fabricated entirely using top down technologies on silicon wafers are presented. The grating consists of 120 nm gold cladding on top of parallel silica nanowires constituting the grating's lines, with gaps between nanowires <10 nm wide at their narrowest point. The grating produces inordinately intense SERS and shows very strong polarization dependence. Reflectance measurements for the optimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
72
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 33 publications
0
72
0
Order By: Relevance
“…19 Even if near-field Raman scattering (surface-enhanced and tip-enhanced Raman scattering) are still challenging techniques for semiconducting nanostructures studies, recent advances exploiting plasmonic effects are promising in view of the careful analysis of narrowest single NWs on specific substrates. 20,21 Here, we report on the UV μ-Raman spectroscopy of a single GaN/AlN NW grown by Molecular Beam Epitaxy (MBE). The bottom part of the GaN NW is covered by an AlN shell whereas the top part has a free lateral surface.…”
Section: Introductionmentioning
confidence: 99%
“…19 Even if near-field Raman scattering (surface-enhanced and tip-enhanced Raman scattering) are still challenging techniques for semiconducting nanostructures studies, recent advances exploiting plasmonic effects are promising in view of the careful analysis of narrowest single NWs on specific substrates. 20,21 Here, we report on the UV μ-Raman spectroscopy of a single GaN/AlN NW grown by Molecular Beam Epitaxy (MBE). The bottom part of the GaN NW is covered by an AlN shell whereas the top part has a free lateral surface.…”
Section: Introductionmentioning
confidence: 99%
“…Near-field localization and studies of SERS on a variety of plasmonic structures have been reported previously by various researchers [11][12][13][14][15]. It is also reported that twodimensional (2D) structures are superior compared to onedimensional (1D) structure.…”
Section: Introductionmentioning
confidence: 73%
“…Thus, engineering the plasmonic structures to achieve densely packed near-field spots or hot spots is a prior must. This optimized structure can be used to explore trace molecular detection, biological sensing, and molecular vibrational studies [1][2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The intercoupling between the bright mode and the dark mode occurs when the near field of one mode overlaps with and excites the near field of the other mode, which can be generated in certain coupled plasmonic nanostructures, such as the symmetry breaking nanocavity-NP system, 21 the nonconcentric ring-disk cavity, 23 the plasmonic nanoshell, 24 NP oligomer chains, 25 nanovoids, [26][27][28][29][30] nanostars, 31 and nanogratings. 32 The plasmonic Fano interference usually results in an asymmetric resonant peak dressing within a broad spectrum. 33 Complex plasmonic nanostructures, in which individual tiny metal NPs are coupled to certain extended metallic structures, are ideal systems for generating both CFE and mode hybridization, such as the plasmonic nanoparticle-in-cavity (PIC) nanoantenna array.…”
Section: Introductionmentioning
confidence: 99%